Does switching trading venues create value? Evidence from Hong Kong - Kwok, Johnny K.H. (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to study whether switching trading venues create value in the Hong Kong stock market. Design/methodology/approach By using an event study, the paper investigates the abnormal returns (AR) earned by firms in the Growth Enterprise Market (GEM) relating to switching to the Main Board (MB). Two measures, turnover of the stock and Amihud’s (2002) illiquidity ratio, are used to examine the liquidity effects. Findings The switch is accompanied by a long-term increase in stock price for low liquidity firms only. High liquidity firms underperform with persistent negative excess returns after switching, while the transient negative excess returns in low liquidity firms reverse gradually. The results further show a significant increase in trading activity for low liquidity firms following the switch, while there is a significant decline in both trading activity and liquidity in firms with high liquidity. The overall results suggest that moving from GEM to the MB is beneficial to low liquidity firms but detrimental to high liquidity firms. Originality/value This study is the first to investigate whether moving from GEM to the MB creates value in the Hong Kong stock market.